Analysis of External Factors Affecting Purchasing Decisions of Scarlett Whitening Products Through the Shopee Platform Using the PESTEL Model : A Study of Students at the University of Sumatera Utara, Medan (International Journal of Economics and Management Research, 2026)
This study aims to analyze external factors influencing purchasing decisions of Scarlett Whitening products through the Shopee platform among students of the University of Sumatera Utara by applying the PESTEL framework. Using a qualitative descriptive–analytical approach within a constructivist paradigm, the research examines how political, economic, social, technological, environmental, and legal factors shape the five stages of the consumer purchasing decision process among digital native consumers. Data were collected through in-depth interviews, focus group discussions, participatory observation, and digital documentation involving 28 student informants from various faculties. The findings reveal that social factors such as peer influence, online reviews, and social media exposure are the most dominant determinants affecting nearly all stages of decision-making. These are followed sequentially by economic, technological, legal, political, and environmental factors. Furthermore, the interaction among factors, particularly socio-economic, socio-technological, and legal-political dynamics, demonstrates that purchasing decisions are not formed in a linear manner. Instead, they emerge through the simultaneous construction of consumer perceptions shaped by multiple external stimuli within a digital marketplace context.